Influence of the metabolic state on the tolerance of Pichia kudriavzevii to heavy metals - Mesquita, Vanessa A. (2016)
This work aims to examine the influence of the metabolic state of the yeast Pichia kudriavzevii on the susceptibility to a metals mixture (5mgL1 Cd, 10mgL1 Pb, and 5mgL1 Zn). Cells exposed to the metals mixture in the presence of 25mmolL1 glucose displayed a higher loss of membrane integrity and proliferation capacity, compared to cells incubated in the absence of glucose. The analysis of the effect of individual metals revealed that glucose increased the toxic effect of Cd marginally, and of Pb significantly. The increased susceptibility to heavy metals due to glucose was attenuated in the simultaneous presence of a mitochondrial respiration inhibitor such as sodium azide (NaN3). ATP-depleted yeast cells, resulting from treatment with the non-metabolizable glucose analogue 2-deoxy-d-glucose, showed an increased susceptibility to heavy metals mixture. Pre-incubation of yeast cells with 1 or 1.5mmolL1 Ca2+ reduced significantly (P<0.05) the loss of membrane integrity induced by the metals mixture. These findings contribute to the understanding of metals mechanisms of toxicity in the non-conventional yeast P. kudriavzevii.